Investigating the match between anthropometric measures and the classroom furniture dimensions in Iranian students with health approach: A systematic review - Maryam Feiz Arefi; Amin Babaei Pouya; Mohsen Poursadeqiyan (Wolters Kluwer Medknow Publications, 2021)
Ergonomics of schools and school furniture is one of the main issues in students' education. The proportion of school furniture to the anthropometric dimensions of students is one of the main ergonomic challenges in schools that affect students' health. This systematic review study aimed to examine the match between anthropometric measures and school furniture dimensions among Iranian students. A systematic review was carried out using databases to Google Scholar, SID, IRANDOC, PubMed, MEDLINE, and ScienceDirect and specific keywords to find papers published before March 2020. The references of seminal studies were also used to extend the search scope. Totally, 11 studies entered the review. The results showed that there was no proportion between classroom furniture and students in schools under study. This lack of proportion was evident at different grades in both boys' and girls' schools. The results showed a lack of proportion between classroom furniture and Iranian students. There is a need to design and procure furniture based on the anthropometric dimensions of the society that will help to health promotion of students. An updated national anthropometric databank of Iranian students can be a step to solve the problem.